Advanced accounting - Griffin, Charles H.; Williams, Thomas Howard; Larson, Kermit D. (Homewood, Ill. : R. D. Irwin ; Georgetown, Ontario : Irwin-Dorsey Ltd., 1980)
The dominant theme of this new edition is to provide a sharply improved presentation of issues of accounting. In the two sections dealing with business combinations and consolidated financial statements, application of the full equity method continues to be the point of reference.
Includes bibliographical references and index.
ne 27/06/2019
Loans
Keywords: Accounting